Effects of foliar Application with Zinc and Boron On fruitset and yield of Sweet cherry (Prunus avium L. var. Bing) - عسكرية, عمار مطيع; Suleiman, Sawsan; Tawakalna, Mahasen (Journal of agricultural, environmental and veterinary sciences, 2021)
The study aims to increase the fruitset percentage of sweet cherry trees, reduce their fall rate and increase fruit retention percentage that reaches the maturity stage. It was conducted during 2019/2020 years at Cherry orchard located in Sargaya- Al- Zabadani area in Rural Damascus, in Syria. the experiment included 4 foliar spray treatments (T1: Control, T2: Zn (100 ppm), T3: B (500 ppm), T4: (100 ppm Zn + 500 ppm B) on sweet cherry trees (Prunus Avium L.) cultivar (Bing) the fruitset percentage, fruit drop percentage, fruiting factor, and yield quantity were calculated for all treatments. The results showed that all treatments (T2, T3, T4) recorded higher fruitset percentage, compared to the control (T1) with no significant differences between (74.83, 76.35, 76.25%) respectively, while the control fruitset percentage (72.76%), and (T4) has achieved the highest percentage of fruiting factor (41.40%) with no significant differences between it and treatment (T3) (37.12%), and the highest yield (19.98 kg), as well as (T2, T3) treatments was (9.39, 10.80 kg/tree) respectively, while the control yield was (5.93 kg/tree). Therefore, it can be considered that treatment (T4) has succeeded in reducing Sweet cherry fruit drop, where the fruit drop percentage didn't exceed (70.27%), and in (T2, T3) treatments was (74.94, 72.99%) respectively, while it reached in the control treatment to (80.64%).
Keywords: Sweet Cherry; Bing; Boron (B); Zinc (Zn); fruitset; fruit drop; yield